Studi Pembuatan Sosis Jamur Tiram Dan Tempe Dengan Penambahan Kenikir Dan Tepung Ubi Kuning - Kurnianingsih kurnianingsih; Citra Dewi Purnamasari (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
The availability of healthy and unhealthy snacks in schools affects the selection of children's snacks. One of the foods that can be processed into snacks/school food is sausage., so that it can be used as healthy food, meat sausage ingredients can be replaced with vegetable ingredients such as oyster mushrooms and tempeh. With the addition of kenikir as fiber and yellow yam flour as adhesive. This study has the objectives of (1) Knowing the level of public preference for sausage products from oyster mushrooms, tempeh, kenikir and yellow yam flour. (2) Knowing the sausage formula from oyster mushroom, tempeh, kenikir and yellow yam flour which is the most preferred by the community. (3) Knowing the process of making sausages from oyster mushrooms, tempeh, The method used in this study is the method of literature, experiments, documentation, and sensory testing. The percentage of using oyster mushrooms and tempeh in making sausages is 90%:10%, 80%:20%, and 70%:30%, of the mushroom weight. The results showed that the sausage product was the most preferred with a ratio of 90% oyster mushrooms and 10% tempeh. As a suggestion, further research is needed to determine the nutritional content of oyster mushroom sausage, tempeh, kenikir and yellow yam flour